THE PLACE OF CHARITY IN ETHICS AT THE SECOND VATICAN COUNCIL - Trautmann, Frederic (Asian Horizons, 2012)
The theme of the place of charity in ethics at the second Vatican Council is not only a research topic in theology but it’s a practical purpose: how is it possible to live better charity into the church today? After a presentation of the origins of this subject and the choices into the definition of the problem, some issues for future research are outlined.